Compactification of low-cost servo valve using buckled tubes and its application - Harada, Shota; Akagi, Tetsuya; Dohta, Shujiro; Kobayashi, Wataru; Koga, Keiichiro; Abdul Nasir, Abd (IEEE, 2017)
In typical pneumatic driving system, the cost of control valve occupies in major cost of the whole system. In addition, in wearable driving system, the mass and size of valve become serious concerns compared with wearable actuator such as a rubber artificial muscle. In our previous study, a low cost and small-sized servo valve using buckled tubes was proposed and developed. In this paper, the compactification of the tested valve for applying a practical use is described. In addition, the position control of rubber artificial muscle using the tested valve is also described.